Polyamide microplastics as better environmental vectors of Cr(VI) in comparison to polyethylene and polypropylene microplastics. (January 2023) - Shao, Xuechun; Zhang, Qi; Liang, Weiyu; Gong, Kailin; Fu, Mengru; Saif, Sadia; Peng, Cheng; Zhang, Wei
Abstract: The adsorption, desorption, and their influence factors of Cr(VI) by microplastics (MPs) in the solution was investigated in this study. The results demonstrated that UV aging promoted adsorption, while the increase of salinity and natural organic matter (NOM) inhibited adsorption. The particle size affected the total Cr(VI) active adsorption sites on MPs, while the pH changed the electrostatic force. The Cr(VI) adsorption by MPs conformed to the pseudo-first and pseudo-second order kinetic models, and was monolayer and inhomogeneous. SEM-EDS, XPS and ATR-FTIR analyses demonstrated that the physical adsorption dominated the adsorption process. Especially, the highest adsorption capacity of Cr(VI) by polyamide (PA) MPs was attributed to their hydrophilic amide groups. However, Cr(VI) was only released from PA MPs, of which desorption rate followed the sequence of seawater (79.5 %) > fresh water (66.6 %) > deionized water (34.8 %). Thus, PA MPs might be non-negligible environmental vectors for the transport of Cr(VI). Graphical abstract: Unlabelled Image Highlights: Compare with PE and PP MPs, PA MPs were better vectors for the transport of Cr(VI). Adsorption impacted by UV aging, MPs' particle size, solution pH, salinity and NOM. Adsorption of Cr(VI) on MPs was dominated by physical effects. PA MPs had the highest desorption capacity in simulated seawater.